Picture this......Studio 64 (Cimarron, New Mexico Cimarron Legend, 1992)
Advertisement for Studio 64 in Cimarron, New Mexico.
Master List item # 34
File location is in the Raton File Cabinet
Keywords: Studio 64; Fine arts; Crafts; Cimarron, New Mexico